PEMBERDAYAAN YAYASAN NURUL IMAN DI KELURAHAN LAWANGAN DAYA PADEMAWU PAMEKASAN DALAM PENINGKATAN KINERJA PENGURUS MELALUI PENDEKATAN MANAJEMAN SUMBER DAYA MANUSIA - Sukma Umbara Tirta Firdaus; Hasbullah Hasbullah; Muhammad Darrin Zuhri (Universitas Pahlawan Tuanku Tambusai, 2022)
The Madura University community service team chose the Nurul Iman Foundation. This foundation is located at RT. 7/ RW. 3 Lawangan Daya Village, Pademawu District, Pamekasan Regency, East Java Province. The reason for the election was because the Chairman of the Foundation had a strong commitment to improving the performance of its administrators. The author has coordinated with the Chair of the Foundation and expressed his willingness to be a partner in this activity. The method of implementing the service in order to implement the solution is carried out by; 1 strengthening and workshops, 2 introduction/strengthening of Human Resources for Foundations, 3 workshops on the method of formulating foundation management and the implementation of training and development of administrators. The results of this activity were concluded from the evaluation of participants' attendance and understanding that more than 70% were positive.